Chemically suppressing redox reaction at the NiOx/perovskite interface in narrow bandgap perovskite solar cells to exceed a power conversion efficiency of 20%. Issue 1 (28th November 2022) - Bian, Hongyu; You, Jiayu; Xu, Cunyun; He, Xiaofeng; Wang, Meng; Yao, YanQing; Zeng, Wenqi; Guo, Pengju; Zhou, Hongyu; Lu, Dengcheng; Dai, Zhongjun; Zhang, Sam; et al.
Abstract : A redox reaction is found at the NiO x /NBG perovskite interface, and a bifacial reduction strategy is proposed for chemically suppressing this. Abstract : NiO x as a type of inorganic hole-transporting layer (HTL) material in narrow bandgap perovskite solar cells (NBG PSCs) showed exceptional stability but suffered a considerably poorer performance compared with NBG PSCs with commonly used PEDOT:PSS as the HTL. Herein, we found that redox reactions would occur at the interface between Ni 3+ on the NiO x surface and the easily oxidized Sn 2+ in the perovskite, causing considerable non-radiative recombination centers. On this basis, we proposed a bifacial reduction strategy at the interface to boost the performance of NBG PSCs. By using a reductive reagent ascorbic acid to reduce the Ni 3+ /Ni 2+ ratio on the surface of NiO x beforehand, the possibility of contact between Ni 3+ on the surface of NiO x and perovskite is chemically reduced substantially, suppressing the redox reaction between them as well as the non-radiative recombination at the interface. By applying this strategy, the device's power conversion efficiency is elevated from 17.81% to 20.48%, with 91% remaining after 1128 hours of storage in a nitrogen-filled glovebox.